P097 Adherence to Guidelines for Preventive Child Health Care in The Netherlands. (15th August 2013) - Lanting, C; Fleuren, M; Broekhuizen, K; Dunnink, T
Abstract : Background: Since 1998, several evidence-based guidelines for Preventive Child Health Care (PCHC) were developed at request of the Dutch Ministry of Ministry of Health Welfare and Sports. The Dutch Centre for Child Health oversees the development, implementation and evaluation of guidelines. Adherence to guidelines is a prerequisite for clients to receive the intended care and benefit. Objective: To assess the extent to which professionals in PCHC adhere to key recommendations of nine PCHC-guidelines. Methods: We undertook a survey among a representative sample of PCHC-professionals (n = 472). Guideline developers selected key activities/recommendations in their guideline. Participants indicated, for each key activity, the proportion of children they applied the activity to. From this, we calculated the proportion of all prescribed key activities the professionals had actually adhered to (i.e. completeness of use). Participants marked obstructers to adhere to the guidelines. Results: 299 (63%) professionals filled-out the questionnaire; 91 doctors, 159 nurses, and 49 medical assistants. Completeness of use varied from 28% to 98% per key activity. Lack of time and lack of client cooperation were often mentioned as obstructers. Discussion: There is room for improvement. Problems in measuring adherence have arisen when key recommendations were not very specific. Implications for Guideline Developers/Users: To enable future monitoring, guideline developers should be specific in formulating key activities, and make sure that, in the guideline, key activities are clearly recognisable. Assessment of adherence is recommended as a way to point out weaknesses in guidelines and their implementation.